KOMUNIKASI ASKRIPTIF TOKOH PUBLIK UNTUK MENCEGAH KEGIATAN SEKS KOMERSIAL TERSELUBUNG - Dodot Sapto Adi; Ana Mariani (UNEJ e-Proceeding)
The article tries to describe ascription communication among the prominent figure intended for covert sexual behavior prevention measures. Making use of descriptive method with subjective approach, it attempts to portray the object of study in natural settings. As such, the data are collected by means of participatory observation, in-depth interview and document study. The data being gathered are then examined using descriptive analysis within ethnographic model. The research found that ascription communication by public prominent leaders has led to prevent sexual behavior among sex workers and their pimps by taking into account their internal as well as external factors. The prominent leader’s interpersonal communication behavior has proven effective because they did so by taking into consideration their counterpart’s social as well as cultural background. Simply saying, their emphatic communication with sexual workers has made the latter felt closer emotionally which eventually work effective for sexual behavior prevention action. This finding illustrates the importance of the prominent leaders’ competence in ascription communication whose main tenets and principles are derived from social phycology.